UTILIZATION OF PINEAPPLE LEATHER WASTE (ANANAS COMOCUS) AS AN OKSALATE ACID SOURCE TO IMPROVE THE EFFECTIVENESS OF Cu (II) IONALIZED ION PHOTOREDUCTION OF TiO2 - Husnul Hatimah; Suryati Suryati (IKIP Mataram, 2013)
A study has been carried out on the effect of the addition of TiO2 photocatalysts and oxalic acid sourced from pineapple skin at various pH and concentrations, to the effectiveness of Cu (II) ion photoreduction catalyzed by TiO2. The photoreduction process was carried out by irradiating the mixture consisting of a solution of Cu (II) ion and TiO2 photocatalyst powder without or in the presence of oxalic acid in a closed reactor equipped with a UV lamp with stirring. The photoreduction process conditions are 50 mL of 10 ppm Cu (II) ion solution (0.157 mmol / L) and varying concentrations of oxalic acid, and 20 mg of TiO2, with a 24-hour reaction time. The photoreduction product was determined based on the difference in the initial Cu (II) ion concentration and the remaining Cu (II) ion concentration in the solution after the photoreduction process was determined by the Atomic Absorption Spectrophotometry (AAS) method. The results showed that the addition of TiO2 could increase the effectiveness of Cu (II) ion photoreduction from 9.03% to 43.22%, which was initiated by the adsorption process. The presence of oxalic acid in pineapple skin in a photoreduction reaction system with greater concentration causes a relatively high increase in Cu (II) ion photoreduction because oxalic acid can prevent recombination of electrons with OH radicals, so that the Cu (II) photoreduction process can run optimally due to the amount of relatively large number of available electrons.